SYSTEMATIC LITERATURE REVIEW USING THE PRISMA APPROACH: FINTECH AND FINANCIAL LITERACY - Upayana Wiguna Eka Saputra; Ketut Vini Elfarosa; Wayan Hesadijaya Utthavi; Anak Agung Ayu Mirah Kencanawati; I Gusti Ayu Astri Pramitari; Eldian Rinaldi (Journal of Applied Finance and Accounting, 2026)
This study synthesizes empirical evidence on the relationship between Financial Technology (Fintech) and digital financial literacy through a PRISMA-based Systematic Literature Review (SLR) of quantitative, Scopus-indexed studies conducted in Asian contexts from 2021 to 2025. The review followed four stages—identification, screening, eligibility, and inclusion—yielding 10 studies for thematic synthesis. Findings converge on two determinant clusters: internal factors (e.g., trust, self-efficacy, foundational financial knowledge) and external enablers (e.g., internet access, institutional quality, regulatory safeguards) that jointly shape the Fintech–literacy nexus. Overall, Fintech can enhance literacy and inclusion, but realized benefits depend on users’ cognitive and procedural capabilities; low literacy diminishes effectiveness and amplifies risks of mis-selling, fraud, and over‑indebtedness in digital environments. Methodologically, the field is dominated by survey-based designs and SEM, with several studies leveraging large-scale household datasets and limited experimentation with machine learning, while qualitative, mixed-methods, and longitudinal approaches remain scarce. Persistent gaps include causal identification, heterogeneous effects across demographic segments and market maturity, lack of standardized Fintech literacy measures, and underexplored mediating and moderating mechanisms. Policy and practice implications emphasize targeted digital literacy interventions, consumer protection by design, and context-sensitive regulation to ensure responsible Fintech adoption, particularly in developing Asian economies where access is expanding faster than capabilities